Palladium membrane reactor for the dehydrogenation of ethylbenzene to styrene - She, Y; Han, J; Ma, YH (ELSEVIER, 2001)
The Pd membrane was made by the electroless plating of Pd on the oxidized porous stainless steel (PSS) support with a 0.5 mum grade. The dehydrogenation of ethylbenzene to styrene was carried out in both the Pd membrane reactor and fixed-bed reactor at temperatures from 450 to 625 degreesC and 1.2 atm pressure with a steam/ethylbenzene ratio of 6.8. As the result of the removal of hydrogen, the ethylbenzene conversion in the Pd membrane reactor was about 10% higher than that in the fixed-bed reactor for temperatures above 600 degreesC. More importantly, the styrene selectivity in the Pd membrane reactor was similar to 15% higher than that in the fixed-bed reactor. (C) 2001 Published by Elsevier Science B.V.
Keywords: PERMEATION